Application of Mechanical Waves in Rock Media for Earthquake Disaster Risk Analysis as an Enrichment of Physics Practicum - Arif Ismul Hadi; Budi Harlianto; Elfi Yuliza; Hana Raihana; Andre Rahmat Al Ansory (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The phenomenon of mechanical waves propagation in rock media is difficult to detect without the use of tools. To